Assessing the constitutional route to federal budget balance - The balanced budget amendment: Toxic, not tonic - Charles J. Whalen (Levy Economics Institute of Bard College, 1995)
Charles J. Whalen evaluates the political and economic arguments in favor of a constitutional amendment requiring a balanced budget and concludes that, although today's federal budget process needs reform, the balanced budget amendment is not a solution. In fact, such an amendment would divert attention from what is really needed, namely, establishing priorities and making difficult decisions concerning the deficit. It would be damaging to both the economic and the political systems of the United States. He recommends budget alternatives - a full-employment budget, an investment budget, a narrowly defined federal capital budget, a biennial budget - that would give the budgeting process more direction and encourage more restraint than the amendment would.
Keywords: 330